Selling local : why local food movements matter - Robinson, Jennifer Meta, 1962-; Farmer, James R. (James Robert) (Indiana University Press, 2017)
In an era bustling with international trade and people on the move, why has local food become increasingly important' How does a community benefit from growing and buying its own produce, rather than eating food sown and harvested by outsiders' Selling Local is an indispensable guide to community-based food movements, showcasing the broad appeal and impact of farmers' markets, community supported agriculture programs, and food hubs, which combine produce from small farms into quantities large enough for institutions like schools and restaurants. After decades of wanting food in greater quantities, cheaper, and standardized, Americans now increasingly look for quality and crafting. Grocery giants have responded by offering "simple" and "organic" food displayed in folksy crates with seals of organizational approval, while only blocks away a farmer may drop his tailgate on a pickup full of freshly picked sweet corn. At the same time, easy-up umbrellas are likely to unfurl over multi-generational farmers' markets once or twice a week in any given city or town. Drawing on prodigious fieldwork and research, experts Jennifer Meta Robinson and James Robert Farmer unlock the passion for and promise of local food movements, show us how they unfold practically in towns and on farms, and make a persuasive argument for how much they deeply matter to all of us.